MarkVCID cerebral small vessel consortium: II. Neuroimaging protocols. Issue 4 (21st January 2021) - Lu, Hanzhang; Kashani, Amir H.; Arfanakis, Konstantinos; Caprihan, Arvind; DeCarli, Charles; Gold, Brian T.; Li, Yang; Maillard, Pauline; Satizabal, Claudia L.; Stables, Lara; Wang, Danny J. J.; Corriveau, Roderick A.; et al.
Abstract: The MarkVCID consortium was formed under cooperative agreements with the National Institute of Neurologic Diseases and Stroke (NINDS) and National Institute on Aging (NIA) in 2016 with the goals of developing and validating biomarkers for the cerebral small vessel diseases associated with the vascular contributions to cognitive impairment and dementia (VCID). Rigorously validated biomarkers have consistently been identified as crucial for multicenter studies to identify effective strategies to prevent and treat VCID, specifically to detect increased VCID risk, diagnose the presence of small vessel disease and its subtypes, assess prognosis for disease progression or response to treatment, demonstrate target engagement or mechanism of action for candidate interventions, and monitor disease progression during treatment. The seven project sites and central coordinating center comprising MarkVCID, working with NINDS and NIA, identified a panel of 11 candidate fluid‐ and neuroimaging‐based biomarker kits and established harmonized multicenter study protocols (see companion paper "MarkVCID cerebral small vessel consortium: I. Enrollment, clinical, fluid protocols" for full details). Here we describe the MarkVCID neuroimaging protocols with specific focus on validating their application to future multicenter trials. MarkVCID procedures for participant enrollment; clinical and cognitive evaluation; and collection, handling, and instrumental validation of fluid samples are described in detail in a companion paper. Magnetic resonance imaging (MRI) has long served as the neuroimaging modality of choice for cerebral small vessel disease and VCID because of its sensitivity to a wide range of brain properties, including small structural lesions, connectivity, and cerebrovascular physiology. Despite MRI's widespread use in the VCID field, there have been relatively scant data validating the repeatability and reproducibility of MRI‐based biomarkers across raters, scanner types, and time intervals (collectively defined as instrumental validity). The MRI protocols described here address the core MRI sequences for assessing cerebral small vessel disease in future research studies, specific sequence parameters for use across various research scanner types, and rigorous procedures for determining instrumental validity. Another candidate neuroimaging modality considered by MarkVCID is optical coherence tomography angiography (OCTA), a non‐invasive technique for directly visualizing retinal capillaries as a marker of the cerebral capillaries. OCTA has theoretical promise as a unique opportunity to visualize small vessels derived from the cerebral circulation, but at a considerably earlier stage of development than MRI. The additional OCTA protocols described here address procedures for determining OCTA instrumental validity, evaluating sources of variability such as pupil dilation, and handling data to maintain participant privacy. MRI protocol and instrumental validation The core sequences selected for the MarkVCID MRI protocol are three‐dimensional T1‐weighted multi‐echo magnetization‐prepared rapid‐acquisition‐of‐gradient‐echo (ME‐MPRAGE), three‐dimensional T2‐weighted fast spin echo fluid‐attenuated‐inversion‐recovery (FLAIR), two‐dimensional diffusion‐weighted spin‐echo echo‐planar imaging (DWI), three‐dimensional T2*‐weighted multi‐echo gradient echo (3D‐GRE), three‐dimensional T2 ‐weighted fast spin‐echo imaging (T2w), and two‐dimensional T2*‐weighted gradient echo echo‐planar blood‐oxygenation‐level‐dependent imaging with brief periods of CO2 inhalation (BOLD‐CVR). Harmonized parameters for each of these core sequences were developed for four 3 Tesla MRI scanner models in widespread use at academic medical centers. MarkVCID project sites are trained and certified for their instantiation of the consortium MRI protocols. Sites are required to perform image quality checks every 2 months using the Alzheimer's Disease Neuroimaging Initiative phantom. Instrumental validation for MarkVCID MRI‐based biomarkers is operationally defined as inter‐rater reliability, test‐retest repeatability, and inter‐scanner reproducibility. Assessments of these instrumental properties are performed on individuals representing a range of cerebral small vessel disease from mild to severe. Inter‐rater reliability is determined by distribution of an independent dataset of MRI scans to each analysis site. Test‐retest repeatability is determined by repeat MRI scans performed on individual participants on a single MRI scanner after a short (1‐ to 14‐day) interval. Inter‐scanner reproducibility is determined by repeat MRI scans performed on individuals performed across four MRI scanner models. OCTA protocol and instrumental validation The MarkVCID OCTA protocol uses a commercially available, Food and Drug Administration‐approved OCTA apparatus. Imaging is performed on one dilated and one undilated eye to assess the need for dilation. Scans are performed in quadruplicate. MarkVCID project sites participating in OCTA validation are trained and certified by this biomarker's lead investigator. Inter‐rater reliability for OCTA is assessed by distribution of OCTA datasets to each analysis site. Test‐retest repeatability is assessed by repeat OCTA imaging on individuals on the same day as their baseline OCTA and a different‐day repeat session after a short (1‐ to 14‐day) interval. Methods were developed to allow the OCTA data to be de‐identified by the sites before transmission to the central data management system. The MarkVCID neuroimaging protocols, like the other MarkVCID procedures, are designed to allow translation to multicenter trials and as a template for outside groups to generate directly comparable neuroimaging data. The MarkVCID neuroimaging protocols are available to the biomedical community and intended to be shared. In addition to the instrumental validation procedures described here, each of the neuroimaging MarkVCID kits will undergo biological validation to determine its ability to measure important aspects of VCID such as cognitive function. The analytic methods for the neuroimaging‐based kits and the results of these validation studies will be published separately. The results will ultimately determine the neuroimaging kits' potential usefulness for multicenter interventional trials in small vessel disease–related VCID.